Pelatihan Penulisan Karya Tulis Ilmiah bagi Guru MTs Muhammadiyah I Malang sebagai Upaya Peningkatan Profesionalitas Guru - Sugiarti Sugiarti; Purwati Anggraini; Musaffak Musaffak (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING OF SCIENTIFIC WRITING FOR TEACHERS OF MTs MUHAMMADIYAH I MALANG AS AN EFFORT TO IMPROVE TEACHER PROFESSIONALITY. The problems of MTs Muhammadiyah 1 Malang teachers in preparing scientific papers include: (1) MTs Muhammadiyah 1 teachers' knowledge to compile scientific papers is still lacking. In fact, it shows that 100% of MTs Muhammadiyah 1 teachers do not yet have the knowledge to compile KTI; (2) the ability of MTs Muhammadiyah 1 teachers in preparing KTI is still low; (3) to increase teacher competence in preparing KTI, training and assistance are needed in the preparation of KTI; (4) the writing process must be carried out by MTs Muhammadiyah 1 teachers to process ideas and design a writing framework in stages and continue to produce products; and (5) the school has never conducted KTI training independently due to limited funding. This activity is carried out through training and mentoring. The form of training carried out is in the form of strengthening (a) understanding knowledge about writing proposals, compiling research reports, and writing scientific articles, (b) this activity is supported by methods of lectures, discussions, questions and answers, and assignments. The mentoring activities are carried out face-to-face which is integrated with training and indirectly through online. The results of the KTI training activities at MTs Muhammadiyah can be argued that (1) teachers' knowledge has increased 70% due to enthusiasm and enthusiasm for participating in the activities; (2) the skills of the teachers in preparing KTI were classified as good because 80% wrote proposals and 20% were articles. (3) the implementation of online assistance in the preparation of KTI still reaches 80%, because online mentoring requires skills to use internet facilities properly.